UML bible - Pender, Tom (Wiley Pub., 2003)
Comprehensive coverage of all aspects of UML (Unified Modeling Language), including use, diagramming notation, the object constraint language, and profiles UML is the industry standard specification for modeling, visualizing, and documenting software projects Includes up-to-date coverage of both UML 1.4 and the new 2.0 UML specifications Thoroughly covers executable UML and testing UML diagrams, making coding more efficient Companion Web site provides additional code samples and updates.